Pengaruh Telenursing Whatsapp Chatbot Terhadap Kepatuhan Minum Obat (OAT) Di Puskesmas Benteng Kota Sukabumi - Risma Sri Mulyati; Erna Safariyah; Amir Hamzah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Health problems that are of global concern are infectious diseases, one of which is tuberculosis (TB). Indonesia is one of the eight countries that contributes the most TB cases worldwide, and is ranked third after India and China (WHO, 2021). Non-compliance with taking medication is the main factor causing TB treatment failure, which reaches 50% (Aisyan, 2018). An innovation that can be done to overcome non-compliance with taking medication is the WhatsApp chatbot telenursing program. The aim of this research is to determine whether there is an effect of WhatsApp chatbot telenursing on medication adherence (OAT) in tuberculosis sufferers at Benteng Sukabumi City Health Center. This research method is experimental research with a pre-experimental one group pre-test post-test research design. The population in this study were all TB-SO and TB-RO patients who were undergoing treatment at Benteng Health Center with a total population of 51 patients. Sampling used a total sample technique according to inclusion and exclusion criteria so that the required sample was 45 respondents. The results of the study showed that there was an increase in medication compliance behavior from before the intervention, 9 respondents were compliant, after the intervention there were 44 respondents who were compliant in taking medication, and the Wilcoxon test results obtained a p-value of 0.000 < 0.05 so that H1 was accepted and existed. The influence of the WhatsApp chatbot telenursing program on compliance with anti-tuberculosis medication (OAT) in tuberculosis sufferers at Benteng Sukabumi City Health Center